Accessibility–equality dynamics in urban blue and green spaces reshape human well-being - Bin Xue; Jianing Zhang; Bingsheng Liu; Marina Alberti; Yufeng Fan; Dong Zhao; Nancy B. Grimm (Proceedings of the National Academy of Sciences, 2026)
As urbanization accelerates, urban blue and green spaces are increasingly recognized as critical nature-based solutions for enhancing human well-being, delivering climate, environmental, and psychological benefits. Yet, the mechanisms by which access to these natural spaces and the equality of access by urbanites in diverse residential locations shape well-being remain poorly understood in the context of sustainable urban governance. Here, we systematically evaluated the spatiotemporal dynamics of urban blue and green space accessibility and equality across 279 Chinese cities from 2000–2100 and assessed their combined effects on well-being. We found that accessibility has a significant positive influence on well-being but follows an inverted-U-shaped pattern with distinct optimal thresholds. By contrast, equality shows a consistent, positive linear relationship with well-being. Although future accessibility is projected to improve, persistently high disparities among different segments of urban populations highlight the urgent need for equity-centered governance of blue and green spaces in cities. This perspective extends current approaches to environmental justice while revealing a structural mismatch between resource abundance and equitable distribution. To address this mismatch, we propose a prioritization framework that emphasizes context-specific, spatially targeted interventions, guided by four key drivers: the natural space to built-up area ratio, urban population size, the proportion of natural spaces with high accessibility, and urban landscape connectivity. By operationalizing these insights in an online toolkit for local governments, this work advances the fields of sustainable urban governance and equitable environmental planning.